Conductive Hydrogel‐Based Electrodes and Electrolytes for Stretchable and Self‐Healable Supercapacitors - Cheng, Tao; Zhang, Yi‐Zhou; Wang, Shi; Chen, Ya‐Li; Gao, Si‐Ya; Wang, Feng; Lai, Wen‐Yong; Huang, Wei (Advanced functional materials, 2021)
Stretchable self‐healing supercapacitors (SCs) can operate under extreme deformation and restore their initial properties after damage with considerably improved durability and reliability, expanding their opportunities in numerous applications, including smart wearable electronics, bioinspired devices, human–machine interactions, etc. It is challenging, however, to achieve mechanical stretchability and self‐healability in energy storage technologies, wherein the key issue lies in the exploitation of ideal electrode and electrolyte materials with exceptional mechanical stretchability and self‐healing ability besides conductivity. Conductive hydrogels (CHs) possess unique hierarchical porous structure, high electrical/ionic conductivity, broadly tunable physical and chemical properties through molecular design and structure regulation, holding tremendous promise for stretchable self‐healing SCs. Hence, this review is innovatively constructed with a focus on stretchable and self‐healing CH based electrodes and electrolytes for SCs. First, the common synthetic approaches of CHs are introduced; then the stretching and self‐healing strategies involved in CHs are systematically elaborated; followed by an explanation of the conductive mechanism of CHs; then focusing on CH‐based electrodes and electrolytes for stretchable self‐healing SCs; subsequently, application of stretchable and self‐healing SCs in wearable electronics are discussed; finally, a conclusion is drawn along with views on the challenges and future research directions regarding the field of CHs for SCs. Conductive hydrogels (CHs) are a new class of soft functional materials that have recently found application in flexible energy storage devices such as batteries and supercapacitors (SCs). Herein, the promise of CHs in this emerging field is demonstrated through summarizing their roles as ideal electrode and electrolyte materials for stretchable and self‐healing SCs.